2009
DOI: 10.1593/tlo.09136
|View full text |Cite
|
Sign up to set email alerts
|

Brain Tumor Stem-Like Cells Identified by Neural Stem Cell Marker CD15

Abstract: In recent years, a small number of cells that have stem cell properties were identified in human gliomas called brain tumor stem cells (BTSCs), which were thought to mainly contribute to the initiation and development of gliomas and could be identified by the surface marker CD133. However, recent studies indicated that the expression of CD133 might be regulated by environmental conditions such as hypoxia and that there might be CD133(-) BTSCs. Genetic mouse models demonstrated that some gliomas originated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 34 publications
4
91
0
Order By: Relevance
“…CD15 + cells had increased expression of stem cell genes, such as Sox2 and Bmi1, and were capable of self-renewal and multilineage differentiation. CD15 + cells also form neurospheres in serum-free, defined medium, while CD15 -cells had minimal neurosphere formation (Mao et al, 2009). A large percent of CD133 + cells co-expressed CD15, but there was also a unique population of CD15 + /CD133 -cells.…”
Section: Cd15mentioning
confidence: 96%
See 1 more Smart Citation
“…CD15 + cells had increased expression of stem cell genes, such as Sox2 and Bmi1, and were capable of self-renewal and multilineage differentiation. CD15 + cells also form neurospheres in serum-free, defined medium, while CD15 -cells had minimal neurosphere formation (Mao et al, 2009). A large percent of CD133 + cells co-expressed CD15, but there was also a unique population of CD15 + /CD133 -cells.…”
Section: Cd15mentioning
confidence: 96%
“…Importantly, 23 out of 24 primary GBMs analyzed contained a subpopulation of CD15 + cells. Cells expressing CD15 that were isolated from CD15 + /CD133 -neurospheres were capable of forming intracranial tumors in mice (Mao et al, 2009). These results together suggest that CD15 is a useful marker for both normal neural stem cells and glioma stem cells, and may identify new CD133 -glioma stem cells.…”
Section: Cd15mentioning
confidence: 99%
“…Many groups identified CD133, Nestin, and sex determining region Y-box 2 (SOX2) as markers to isolate NSCs which maintain the essential properties of stem cells (self-renewal and ability to differentiate into multiple progeny) [115][116][117][118]. Using the NSC neurosphere culturing method, CD133 and/or CD15 have also been found to be expressed on BTSCs from GBM, medulloblastoma, ependymoma, and astrocytoma tumors [118][119][120]. Interestingly, Singh et al (2003) found CD133 + cells to be tumor initiating, whereas CD133 À cells could not initiate a tumor or self-renew in a mouse xenograft model [118,121].…”
Section: The Role Of Astrocytes In Brain Tumor Stem Cell Biologymentioning
confidence: 99%
“…Overall, 19-29 % of cells in glioblastomas and 6-21 % of cells of medulloblastomas are reported to be CD133+ and tumorigenic [33]. Recently, several groups have suggested that CD15 (stage specific embryonic antigen 1 or SSEA-1), which is expressed on neural progenitor and stem cells, may be a better marker than CD133 of tumor-initiating cells in MB, glioma, and ependymoma [42][43][44]. Hansford et al has recently identified tumor initiating cells from NB bone marrow metastases that have several properties of cancer stem cells including the expression of stem cell markers, the ability to self renew and the capability to form metastatic NB in immunodeficient animals with as few as 10 cells [45].…”
Section: Cancer Stem Cells In Neuroblastoma Tumorigenicitymentioning
confidence: 99%